The Effects of Wireless Micro Current Stimulation for Partial Thickness Burn Injury Treatment - Utama, Defry; Wardhana, Aditya (Jurnal Plastik Rekonstruksi, 2012)
Backgrounds: The body has its own bioelectric system that influences wound healing. Wireless Micro Current Stimulation (WMCS) or Electrical Stimulation (ES) is defined as the use of an electrical current to transfer energy to a wound. The type of electricity transferred is controlled by the electrical source. Although scarce, there have been studies proposing that this type of electricity increased healing rate of various wounds. However the effect of this electrical stimulation on burn wounds has not yet been studied.Patient and Methods: We present case series of superficial and deep partial thickness burns treated with ES and examine its effect on healing process. Six cases of second degree burn admitted to Cipto Mangunkusumo General Hospital (RSCM) from March–May 2011. They were chosen randomly to be treated with WMCS/ES. We applied the stimulation on the wound one hour daily. The wound was cleansed conventionally with moist gauze before and after the stimulation.Results: All the patients reported that they feel comfort during and after the application. We found epithelialization within 6 to 9 days. However we cannot determined if the WCMS/ES induce faster wound healing, because we do not compare it with other treatment. Summary: From six cases that we studied, we concluded that, the use of this WCMS/ES could have an effect of the epithelialization within 6-9 days. All the patients reported that they feel comfort during and after the application of WMCS/ES.